2017
DOI: 10.1128/aac.01391-16
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Human and Mouse Soluble Scavenger-Like CD6 Lymphocyte Receptor in a Lethal Model of Polymicrobial Sepsis

Abstract: Sepsis still constitutes an unmet clinical need, which could benefit from novel adjunctive strategies to conventional antibiotic therapy. The soluble form of the scavenger-like human CD6 lymphocyte receptor (shCD6) binds to key pathogenic components from Gram-positive and -negative bacteria and shows time-and dose-dependent efficacy in mouse models of monobacterial sepsis. The objective of the present work was to demonstrate the effectiveness of infusing mouse and human sCD6 by different systemic routes, eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…They were chosen based on previously reported information showing that Spα (4) and CD6 (68) but not CD5 (9) exhibit broad bacterial-binding properties. While the authors confirmed the work on Spα and CD5, they were unable to replicate that on CD6.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They were chosen based on previously reported information showing that Spα (4) and CD6 (68) but not CD5 (9) exhibit broad bacterial-binding properties. While the authors confirmed the work on Spα and CD5, they were unable to replicate that on CD6.…”
mentioning
confidence: 99%
“…While the authors confirmed the work on Spα and CD5, they were unable to replicate that on CD6. Exclusively based on a single experimental evidence, the authors cast doubt on the well-documented bacterial-binding properties of CD6 (68). These properties were unveiled by using a recombinant soluble form of human CD6 (rshCD6) encompassing from D 25 to M 400 and, indistinctly, produced in different mammalian cell expression systems (NSO, HEK293-EBNA, and CHO cells).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Production and purification of endotoxin-free purified recombinant shCD6 and shCD5 proteins (in PBS with 10% glycerol, pH 7.4) from SURE CHO-M cell line clones was done following previously reported methods. 23 Human (HSA) and bovine (BSA) serum albumin were from Sigma-Aldrich.…”
Section: Cells and Proteinsmentioning
confidence: 99%
“…Construction and production of recombinant adenoassociated virus (AAV) Construction and production of recombinant AAV8 virus expressing soluble mouse CD6 (AAV-smCD6) or luciferase (AAV-Luc) proteins under the control of a chimerical liver-specific (EalbAAT) promoter was carried out as previously reported. 23 elisA assays The plasma levels of shCD6 and smCD6 were quantified with the human soluble CD6 PicoKine ELISA Kit (Boster Bio) and the DuoSet mouse CD6 kit (R&D Systems), respectively, following manufacturer's instructions. bromodeoxyuridine incorporation and treg suppression assays Detection of in vivo proliferating cells with bromodeoxyuridine (BrdU) was performed as reported elsewhere.…”
Section: Generation Of Shcd6lckeµ Transgenic Micementioning
confidence: 99%